Improving food safety on the farm: Experimental evidence from Kenya on agricultural incentives and subsidies as public health investments - Hoffmann, Vivian; Jones, Kelly M. (International Food Policy Research Institute, 2018)
Evidence continues to mount that foodborne illness imposes a staggering health burden in developing countries. However, standard approaches used by developed country governments to ensure food safety are not appropriate in settings where regulatory enforcement capacity is weak and most firms are small and informal. Thus, interventions to improve food safety in developing countries must take into account the constraints and incentives faced by producers in these countries. In this paper, we test the impact of two such interventions: subsidies for technologies that improve food safety and price premiums for safer produce. We examine the case of on-farm control of aflatoxin, a carcinogenic toxin linked to child stunting that is produced by a fungus commonly found on maize and groundnut. We show that compared to Kenyan farmers who produce maize only for their family’s own consumption, Kenyan farmers who produce maize for sale are less likely to undertake post-harvest practices that increase the unobservable quality of aflatoxin safety. Employing randomized discount vouchers, we find that willingness to pay for a new post-harvest technology to prevent aflatoxin contamination is significantly lower among market producers than subsistence farmers. However, we find that take-up of the technology among market producers increases when they have the opportunity to sell aflatoxin-safe maize at a premium a few months after harvest. Using take-up rates from the experiment, we model the impacts of public subsidies and market incentives for aflatoxin control. We find that subsidization of aflatoxin control technologies is a cost-effective strategy for reducing liver cancer and possibly also for reducing stunting in children. The most cost-effective technologies considered are widely adopted by both subsistence and market producers, implying little additional impact of a price premium on food safety.